Photocatalytic Hydrogen or Oxygen Evolution from Water over S- or N-Doped TiO2 under Visible Light - Kazumoto Nishijima; Takaaki Kamai; Naoya Murakami; Toshiki Tsubota; Teruhisa Ohno (International Journal of Photoenergy)
S- or N-doping of TiO2 powder having an anatase or rutile phase extended the photocatalytic activity for water oxidation and reduction under UV light and visible light irradiation. For the reduction of water, anatase-doped TiO2 showed higher level of activity than that of doped TiO2 having a rutile phase using ethanol as an electron donor. Furthermore, the activity level of S-doped TiO2 for hydrogen evolution was higher than that of N-doped TiO2 photocatalysts under visible light. Photocatalytic oxidation of water on doped TiO2 having a rutile phase proceeded with fairly high efficiency when Fe3+ ions were used as electron acceptors compared to that on doped TiO2 having an anatase phase. In addition, water splitting under visible light irradiation was achieved by construction of a Z-scheme photocatalysis system employing the doped TiO2 having anatase and rutile phases for H2 and O2 evolution and the I−/IO3− redox couple as an electron relay.